PENGARUH MODAL KERJA, PERILAKU KEWIRAUSAHAAN DAN KETERAMPILAN ADMINISTRASI TERHADAP PERKEMBANGAN USAHA PARA PEDAGANG DI PASAR BARU KOTA KUNINGAN - Saeful Rahmat, Pupu; ., Iskandar (Economicus, 2018)
The problem in this research is lack of business development of actors informal sector in Pasar Baru - Kuningan District. The purpose of this study is as follows: (1) to determine the effect of simultaneously working capital, entrepreneurial behavior and skills to manage the administration of the development of the informal sector in Pasar Baru Kuningan; (2) to determine the effect of working capital to the development of the informal sector in Pasar Baru Kuningan; (3) to determine the effect of entrepreneurial behavior to the of the informal sector in Pasar Baru Kuningan; (5) to determine the effect on the development of skills to manage the administration of informal sector businesses in Pasar Baru - Kuningan. The method used in this research is quantitative method type survey. The hypothesis of this study are Working capital, entrepreneurial behavior and skills to manage the administration of influence simultaneously to the development of informal sector enterprises. Research results are: working capital, entrepreneurial behavior and skills to manage the administration jointly influence simultaneously to the development of informal sector businesses in Pasar Baru-Kuningan. Working capital has a positive and significant impact on the development of informal sector businesses in Pasar Baru-Kuningan. This means that the presence of additional working capital will also increase business development in the informal sector of Pasar Baru – Kuningan District.